1993
DOI: 10.1111/j.1559-1816.1993.tb01074.x
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Racial Attitudes

Abstract: Factor analyses of responses from white (N = 260) and black (N = 81) college students in two neighboring universities were utilized to develop contemporary measures of racial attitudes and of the degree of interracial contact experienced by blacks and by whites. Two sets of 112 attitudinal statements were utilized for the initial factor analyses, one set for black respondents and one for whites. About 60% of the items in the two sets were identical or the same except that the racial designations were revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
367
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(383 citation statements)
references
References 43 publications
11
367
0
5
Order By: Relevance
“…Plant and Devine (1998) conducted a series of studies in which they showed that the scales are reliable and provided evidence regarding the scales' convergent, discriminant, and predictive validity. For example, they demonstrated that scores on the IMS were highly correlated with traditional measures of prejudice, including the Attitude Towards Blacks scale (ATB; Brigham, 1993) and the Modern Racism Scale (MRS; McConahay, 1986), such that higher levels of internal motivation were associated with lower prejudice scores. The EMS, in contrast, was only modestly correlated with traditional prejudice measures, such that high levels of external motivation were associated with higher prejudice scores.…”
Section: Self-determination and Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant and Devine (1998) conducted a series of studies in which they showed that the scales are reliable and provided evidence regarding the scales' convergent, discriminant, and predictive validity. For example, they demonstrated that scores on the IMS were highly correlated with traditional measures of prejudice, including the Attitude Towards Blacks scale (ATB; Brigham, 1993) and the Modern Racism Scale (MRS; McConahay, 1986), such that higher levels of internal motivation were associated with lower prejudice scores. The EMS, in contrast, was only modestly correlated with traditional prejudice measures, such that high levels of external motivation were associated with higher prejudice scores.…”
Section: Self-determination and Self-regulationmentioning
confidence: 99%
“…2 In all three studies, we assess explicit race bias using Brigham's (1993) ATB, a highly reliable and valid measure. To assess implicit race bias, we use a sequential evaluative priming procedure in Study 1 (Dovidio, Kawakami, Johnson, Johnson, & Howard, 1997;Fazio et al, 1995) and the Implicit Association Test (IAT; Greenwald et al, 1998) in Studies 2 and 3.…”
Section: Self-determination and Self-regulationmentioning
confidence: 99%
“…Modern explicit attitude measures, for example, often infer attitudes by aggregating levels of agreement to a variety of propositional statements. For example, items on the Modern Racism Scale (Brigham, 1993) concern beliefs about race-related issues such as support for affirmative action. The richness of these explicit measures may actually be a hindrance to observing strong implicit -explicit consistency because implicit measures are presumed to reflect relatively simple associative relations such as the association of racial groups with positive or negative evaluation, rather than the rich nuance of support or disapproval of racerelevant political issues.…”
Section: Measurement Correspondencementioning
confidence: 99%
“…These findings suggest that adjustment to internal standards may be a stronger moderator than adjustment to external norms. Finally, Ziegert and Hanges (2005) employed only the external subscale and found it moderated the relationship between a race IAT and the attitudes towards blacks scale (Brigham, 1993), but not the more subtle modern racism scale (McConahay, 1986). This latter finding suggests that external motivation may be a significant moderator only for blatant explicit measures that clearly elicit social desirability concerns and not for explicit measures including more subtle but socially acceptable items.…”
Section: Adjustmentmentioning
confidence: 99%
“…Explicit race bias was measured using Attitudes Toward Blacks scale (Brigham, 1993). The scale included items like ''Generally, Blacks are not as smart as Whites'' and ''It is likely that Blacks will bring violence to neighborhoods when they move in.''…”
Section: Explicit Race Biasmentioning
confidence: 99%